Dependence of regenerated sensory axons on continuous neurotrophin-3 delivery - Hou, Shaoping; Nicholson, LaShae; Motsch, Melanie; Blesch, Armin (The journal of neuroscience, 2012)
Previous studies have shown that injured dorsal column sensory axons extend across a spinal cord lesion site if axons are guided by a gradient of neurotrophin-3 (NT-3) rostral to the lesion. Here we examined whether continuous NT-3 delivery is necessary to sustain regenerated axons in the injured spinal cord. Using tetracycline-regulated (tet-off) lentiviral gene delivery, NT-3 expression was tightly controlled by doxycycline administration. To examine axon growth responses to regulated NT-3 expression, adult rats underwent a C3 dorsal funiculus lesion. The lesion site was filled with bone marrow stromal cells, tet-off-NT-3 virus was injected rostral to the lesion site, and the intrinsic growth capacity of sensory neurons was activated by a conditioning lesion. When NT-3 gene expression was turned on, cholera toxin β-subunit-labeled sensory axons regenerated into and beyond the lesion/graft site. Surprisingly, the number of regenerated axons significantly declined when NT-3 expression was turned off, whereas continued NT-3 expression sustained regenerated axons. Quantification of axon numbers beyond the lesion demonstrated a significant decline of axon growth in animals with transient NT-3 expression, only some axons that had regenerated over longer distance were sustained. Regenerated axons were located in white matter and did not form axodendritic synapses but expressed presynaptic markers when closely associated with NG2-labeled cells. A decline in axon density was also observed within cellular grafts after NT-3 expression was turned off possibly via reduction in L1 and laminin expression in Schwann cells. Thus, multiple mechanisms underlie the inability of transient NT-3 expression to fully sustain regenerated sensory axons.
Gesehen am 07.11.2018